THE DESIGN OF LOCAL WISDOM-BASED ECOTOURISM DESTINATION IN KUPANG CITY - Antonio E.L. Nyoko; Apriana H.J. Fanggidae (Universitas Nusa Cendana, 2015)
Kupang is the right region for the ecotourism destination in NTT because it has three superiorperspectives i.e. first; ecotourism as a product (diverse natural and cultural resources), second;ecotourism as a market; the products are produced by farmers, not only marketed to traditionalmarkets but also to domestic and international market, and third; ecotourism as a approach todevelopment, it needs cooperation among the government authorities, society and entrepreneurs todevelop the potential of local communities becoming the potential of ecotourism which is ready tooffered to the potential market. This research aims to formulate the implementation strategies oflocal wisdom-based ecotourism destinations model using SWOT (strength, weakness, opportunity,threat) analysis. Results of the study indicated that Kupang has diverse natural attractions such asbeach, mountain and culture that can be promoted as local wisdom-based ecotourism. The design ofthe ecotourism development in Kupang City noticed the local wisdom which consist of two aspects,tangible local wisdom and intangible local wisdom and they are grouped into similar industry in aregion. Varied industrial activity, called agglomeration, divided into 4 clusters ; education, culture,environment and aesthetics. Recommendation from the result of this research was all attractionsthat had been identified and most of them had not developed yet, needed to be noticed from thegovernment, private sector, NGOs, academics and society in creation of a sustainable tourismdevelopment program. Keywords: Ecotourism, Local wisdom-based, SWOT